2015
DOI: 10.1111/jvim.13586
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation Enhances Bleomycin Efficacy in Cats with Periocular Carcinoma and Advanced Squamous Cell Carcinoma of the Head

Abstract: BackgroundAdvanced carcinoma of the head represents a substantial health problem in cats for local control and overall survival.ObjectivesEvaluate the capability of electrochemotherapy (ECT) to improve bleomycin efficacy in cats with periocular carcinoma and advanced carcinoma of the head.AnimalsTwenty‐one cats with periocular carcinoma (17 squamous cell carcinoma [SCC] and 4 anaplastic carcinoma) and 26 cats with advanced SCC of the head.MethodsNonrandomized prospective controlled study. Periocular carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 28 publications
(53 reference statements)
7
57
1
2
Order By: Relevance
“…In an attempt to enhance the cytotoxic effects of intralesional bleomycin, Pasquali and colleagues tested the application of electroporation (ECT) immediately before injection (Pasquali, Spugnini, & Baldi, ). In earlier studies, ECT was shown to disrupt cell membrane and improve drug uptake by the tumor cells (Spugnini et al, ; Spugnini & Baldi, ). Consistent with these findings, the group achieved satisfactory results but it must be emphasized that this study was limited to a single patient.…”
Section: Intralesional Treatment Options Of Kamentioning
confidence: 99%
“…In an attempt to enhance the cytotoxic effects of intralesional bleomycin, Pasquali and colleagues tested the application of electroporation (ECT) immediately before injection (Pasquali, Spugnini, & Baldi, ). In earlier studies, ECT was shown to disrupt cell membrane and improve drug uptake by the tumor cells (Spugnini et al, ; Spugnini & Baldi, ). Consistent with these findings, the group achieved satisfactory results but it must be emphasized that this study was limited to a single patient.…”
Section: Intralesional Treatment Options Of Kamentioning
confidence: 99%
“…These trials, beside yielding an extremely high percentage of responders among the patients were the proof of concept that ECT could be highly effective as first line of treatment, rather than being confined to the palliation of cutaneous metastases as in humans (Campana et al, ; Ricotti et al, ; Kreuter et al, ). These preliminary findings rapidly led to the mounting of several phase II trials on pets affected by different cancers, including sarcomas, mast cell tumors, melanoma, lymphoma and carcinomas of different types, and locations (Tozon et al, , ; Baldi and Spugnini, ; Spugnini et al, ,b, ,c,d,e,f, ,c,d,e,f, , , ,c, , ; Kodre et al, ). All the studies reported minimal side effects, ease of treatment and response rates superior to surgery alone and comparable to adjuvant radiation therapy.…”
Section: Veterinary Experience With Ectmentioning
confidence: 99%
“…Эффект после электропорационной терапии отмечен в 89% случаев (у 21 животного имелась необратимая реакция, у 2 -частичная), в то время как в контроле (лечение только блеомицином) -только у 33% кошек. Среднее время прогрессии в группе электрохими-отерапии составляло 30,5 мес, а в контроле -3,9 мес (р<0,0001) [31].…”
Section: рис 2 схема принципа электропорацииunclassified